Beyond simple T/V distinctions: Investigating Balti personal pronouns as markers of social distance, authority, and communal solidarity - Zulfiqar Ali; Muhammad Mustafa; Dr. Muhammad Essa (Journal of Language, Literature, Social and Cultural Studies, 2026)
The study was aimed at examining the sociolinguistic role of the pronouns in the Balti language and how they are used to express power and solidarity relations within the Balti community in Baltistan. Using the theoretical framework of Brown and Gilman (1960), this qualitative study uses a purposive sampling technique, whereby it applied of semi-structured interviews and observation data collected among native speakers (Balti Poets). It is in the analysis of specific variants of pronouns, including formal and informal pronoun forms of "you" (e.g. Yaang and Khyang) that speakers strategically use to maneuver in social discourses. Results showed that the use of pronouns is regulated by the contextual factors such as age, social status, formality of the environment, and the type of relationship between these people. Formal pronouns indicate respect and power (authority) to elder ones and those in higher positions vice versa, the informal pronouns promote authority, intimacy and equality (solidarity) among equals and family members within discourses. The study highlighted that Balti pronouns play a pivotal role in shaping social identity and upholding the cultural rules of respect, integrity and strengthening social ties in the targeted situations. The study would be supportive for the researchers preserve the Balti language and further advance the sociolinguistic studies by illustrating the ever-changing nature of language and social structure in a distinctly unique settings accordingly.